Tren Konsumsi Mahasiswa di Era Dompet Digital melalui Integrasi Model TAM dan UTAUT - Johanis M, Andrew Ridow; Nurdiana, Nurdiana; Sugiantoro, Muh Nurhidayat; Wongso, Sampurna Budi (Journal of Business and Economics Research (JBE), 2025)
The development of financial technology has transformed consumption patterns among young generations, particularly students as early adopters of digital wallets. This study aims to analyze factors influencing student consumption trends in the digital wallet era by integrating Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT). Using a quantitative approach with cross-sectional design, data were collected from 63 students at Universitas Dipa Makassar through online surveys. Multiple regression analysis revealed Perceived Usefulness as the most dominant predictor (β = 0.463) of digital wallet usage preferences, demonstrating 64.7% predictive capability. The findings confirm the significant mediating role of Usage Preference in the relationship between technology adoption factors and consumption pattern changes, explaining 52.1% of behavioral variance. GoPay's market dominance with an 82.5% adoption rate reflects strong network effects within Indonesia's digital payment ecosystem. Despite the existence of an intention-behavior gap, this study provides strategic insights for digital wallet service providers and policymakers in optimizing adoption strategies that are responsive to digitally native generation characteristics.